Izboljševanje prostorske ločljivosti Landsat 8 termograma v luči mestnega toplotnega otoka - Grujić, Jaša Veno (Revija za geografijo, 2020)
More than half of today's global human population lives in urban areas. As a result, built-up areas are expanding and thus creating the urban heat island (UHI) effect. This effect is known as one of the most widely recognized local meteoroidal phenomenon caused by anthropogenic activity. Owing to global climate change, the UHI phenomenon is intensifying, which poses even bigger threat to vulnerable social groups of citizens. It is also affecting the urban economy, especially energy consumption. For successful planning of mitigation and adaptation measures, urban design and sustainable development, analytical studies of the UHI phenomenon, using a combination of in-situ measurement data and remote sensing data, are crucial. When using the latter, we are often limited by the spatial resolution of the corresponding thermal bands.
Keywords: daljinsko zaznavanje; mobile measurements; mobilne meritve; remote sensing; satelitske podobe; satellite imagery; termični kanal; thermal band